Museum of Toba Caldera with Metaphore Architecture Approach - M. Solin, Thareq Muhammad; Ginting, Nurlisa (Jurnal Koridor, 2020)
Lake Toba was formed by a volcanic explosion called Mount Toba. It erupted three times, making the caldera with the crater beneath a lake and an address for natural attractions. The purpose of this study is to provide information on the history of Lake Toba visitors. So that tourists can see information at once on Lake Toba, supporting facilities such as museums are needed. The museum is a place of education and recreation, following the tourist area's context and making visitors not bored with monotonous education. Designing museum uses the Intangible Methapore theme, which starts from ideas, concepts, or human nature such as; individualism, communication, naturalism, tradition, and culture.